MpsAB is important for Staphylococcus aureus virulence and growth at atmospheric CO2 levels - Sook-Ha Fan (Nature Portfolio, 2019)
The mechanisms behind CO2 dependency in non-autotrophic bacterial isolates are unclear. Here the authors show that the Staphylococcus aureus mpsAB operon is crucial for growth at atmospheric CO2 levels, and provide evidence indicating that MpsAB represents a bicarbonate concentrating system.